Cognitive Aspects of Relative Clause Production In Oral and Written Narratives - Pu, Ming-Ming (Investigationes Linguisticae, 2019)
The present study aims to investigate relative clause production in Chinese and English from a cognitivefunction approach that explores underlying cognitive, semantic, and discourse-pragmatic factors operative in discourse processing. With this approach we are able to account for both general and specific distributional patterns of RCs between the two languages on the one hand and between speech and writing on the other, using narrative data elicited from native speakers of both languages.